The electromagnetic mass of the proton - Gimsa, Andreas (International Journal of Scientific Research and Management (IJSRM), 2024)
In the proton there is an energy equilibrium between the relativistic energy of its positron and the magnetic energies between its two magnetic poles and between its magnetic poles and its positron.